2011
DOI: 10.1002/acr.20433
|View full text |Cite
|
Sign up to set email alerts
|

A model to predict cardiovascular events in patients with newly diagnosed Wegener's granulomatosis and microscopic polyangiitis

Abstract: Objectives To create a prognostic tool to quantify the 5 year cardiovascular (CV) risk in patients with newly diagnosed Wegener’s granulomatosis (WG) and microscopic polyangiitis (MPA) without pre-morbid CV disease. Methods We reviewed CV outcomes during the long term follow up of patients in the first 4 European Vasculitis Study Group (EUVAS) trials of WG and MPA. CV events were defined as: CV-death, stroke, myocardial infarction, coronary artery bypass graft, or percutaneous coronary intervention. Logistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
82
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(95 citation statements)
references
References 39 publications
(53 reference statements)
7
82
1
5
Order By: Relevance
“…After 12 months, the major cause of death was cardiovascular disease, presumably related to ESRD. Early cardiovascular events have been previously reported in association with ANCA vasculitis and are postulated to be related to active inflammation as well as underlying atherosclerosis (21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After 12 months, the major cause of death was cardiovascular disease, presumably related to ESRD. Early cardiovascular events have been previously reported in association with ANCA vasculitis and are postulated to be related to active inflammation as well as underlying atherosclerosis (21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…The renal biopsy specimens of 153 patients were reviewed. The median number of glomeruli examined per biopsy specimen was 16 (IQR, [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. The pattern of glomerular injury according to the EUVAS schema was categorized as sclerotic in 32% of cases, focal in 6%, crescentic in 43%, and mixed class in 6%.…”
Section: Cohort Description and Outcomesmentioning
confidence: 99%
“…140 This study also showed that independent determinants of cardiovascular outcome were: older age (OR 1.45, 95% CI 1.11 to 1.90), diastolic hypertension (OR 1.97, 95% CI 0.98 to 3.95) and PR3-ANCA (OR 0.39, 95% CI 0.20 to 0.74). 140 Annual review of traditional Framingham risk factors is appropriate.…”
Section: Statement 13mentioning
confidence: 68%
“…К не-зависимым факторам риска ССЗ относят пожилой возраст, диастолическую гипертензию, специфичность АНЦА к ПР3 [34]. Рекомендация 14.…”
Section: рекомендация 13 рекомендована периодическая оцен-ка риска сunclassified